Identification of TNFAIP8 as an Immune-Related Biomarker Associated With Tumorigenesis and Prognosis in Cutaneous Melanoma Patients - Sun, Yuliang; Zhao, Jianxiong; Sun, Xiaoru; Ma, Guangxin (Frontiers in Genetics, 2021)
Tumor necrosis factor-α-induced protein 8 (TNFAIP8) is a member of the TIPE/TNFAIP8 family which is associated with inflammation and tumorigenesis. The potential role of TNFAIP8 in tumor immune microenvironment in skin cutaneous melanoma (SKCM) has not yet been investigated. The TNFAIP8 expression was evaluated via Gene Expression Profiling Interactive Analysis (GEPIA). We also evaluate the influence of TNFAIP8 on overall survival via GEPIA and PrognoScan. After GO and KEGG pathways analysis, the correlation between TNFAIP8 expression level and immune cell or gene markers of immune infiltration level was explored by R-language. The result showed TNFAIP8 expression was significantly reduced in SKCM in comparison with normal control. In SKCM, TNFAIP8 expression in higher levels was associated with the better overall survival. High expression of TNFAIP8 was positively correlated with immune score and promoted immune cell infiltration in SKCM patients. TNFAIP8 can be as a positive prognosis marker or new immunotherapy target in SKCM.